Aspectos físicos de las técnicas elastográficas basadas en ultrasonido. - Saavedra, Ana Cecilia; Guerrero, Jorge; Pinto, Joseph; Gonzaléz, Eduardo; Castañeda, Benjamín (Carcinos)
Biopsy is the microscopic analysis that verifies the presence of cancer and, in spite of being invasive and having sampling errors; it is still the standard of care nowadays. On the other hand, technology has greatly improved current medical imaging. However, an infallible imaging modality does not exist yet for the detection and diagnosis of cancer. In the last 20 years, elastography has emerged as a set of techniques which seek to detect and diagnose the cancer based on the analysis of the stiffness o f the tissue. Since cancer changes the elasticity of the tissue, elastographic techniques show qualitative and quantitative images of elasticity. Specifically for ultrasound, the most important qualitative techniques are: compression e lastography, acoustic radiation force impulse imaging and sonoelastography; while the quantitative techniques are: shear wave elasticity imaging, crawling wave sonoelastography, supersonic shear imaging and vibroelastography. The objective of this work is to present the physics phenomenon behind each technique.